Characterization of Phosphate Solubilizing Streptomyces as a Biofertilizer - Mathurot Chaiharn (Science Faculty of Chiang Mai University, 2019)
Three hundred and twenty bacterial isolates were screened for phosphate solubilizing activity on Pikovskaya’s agar medium. All of the bacterial isolates were able to solubilize bound phosphate in vitro. Streptomyces isolate L3, Streptomyces isolate KT 6-4-1 and Streptomyces isolate ST 3 were selected as the three promising phosphate solubilizing bacteria. Selected isolates were further investigated for optimum phosphate solubilization ability under various sources of phosphorus such as tricalcium phosphate (TCP), aluminium phosphate (AP) and rock phosphate (RP), and varying temperature, pH and incubation periods. Solubilization activities were maximum at 37°C, pH 7.0 and incubation period of 15 days. All bacterial isolates exhibited optimum phosphate solubilization at TCP medium. Selected isolates enhanced the growth of rice plants under greenhouse conditions relative to uninoculated control. Streptomyces isolate KT 6-4-1 significantly increased rice root length (9.45 cm) followed by Burkholderia isolate SN 5.4 (8.71 cm) and Bacillus isolate MC15 (8.27 cm) in comparison with uninoculated plants (5.53 cm). Highest plant height (23.66 cm) was observed in rice inoculated with Streptomyces isolate 4-2-1 followed by Burkholderia isolate SN 5.4 (23.24 cm) and Bacillus isolate MC 8 (21.64 cm). In addition, Bacillus isolate W9 increased the dry mass of rice (0.16 g), followed by Bacillus isolate MC15 (0.15 g). Based on cultural and morphological characterization, and 16S rDNA sequencing, Streptomyces isolate KT 6-4-1 was identified as Streptomyces sp. with 96.57 % similarity. The significant increase in plant height and dry weight and their ability to colonize the rhizosphere demonstrate the potential of these Streptomyces as plant growth-promoting inoculant for rice. However, further assessment is recommended to determine the inoculum production and their inoculation effect on plant growth in vivo.